ANALISIS PENGARUH PROMOSI TERHADAP MINAT KULIAH PADA UNIVERSITAS ICHSAN GORONTALO - Cahya Pradipta Abdussamad; Risti Puspita Sari Hunowu; Fitrah Jayanti meiliany Mbuinga (UNIVERSITAS STEKOM, 2024)
This research aims to analyze the impact of promotions on interest in studying at Ichsan University, Gorontalo. As Competition in Higher Education Continues to Increase, Effective Support Strategies Are Key to Attracting Prospective Students. The method used in this research is a questionnaire survey distributed to new students entering Ich San Gorontalo University. The data obtained were analyzed using simple regression analysis techniques and statistical tests to determine the relationship between promotion variables and interest in studying. Research results show that UIG promotions carried out through social media are very effective in attracting the attention of prospective students. The most widely used media are Instagram and flyers/brochures which are proven to be more effective than other platforms. However, there is a need to increase the effectiveness of advertising, especially in relation to the relevance of the information conveyed. UIG Can Significantly Increase Applicant Interest by Improving Advertising Content to Match the Needs of Prospective Students